Vibration analysis of nonlinear systems modelled by a mass attached to a stretched elastic wire. Issue 4 (3rd July 2016) - Pirbodaghi, Tohid; Hoseini, Seyed Hamed; Akbari, Samin
Abstract: Herein, an accurate approximate analytical solution for oscillation of nonlinear systems modelled by a mass attached to a stretched elastic wire is derived using the homotopy analysis method and homotopy Pade technique. Approximate analytical expressions for the frequency and displacement with respect to time are obtained. Comparison between the presented results and numerical solutions shows that the first-order approximation of homotopy Pade technique leads to accurate results.